The Influence of Casting Machine Speed in Cellulose Acetate Membrane Preparation - Luqman Buchori (Chemical Engineering Diponegoro University, 2010)
Membranes are being increasingly used as a valuable separation tool in laboratory as well as in industrial processes. Continual development of new membrane materials is crucial to sustain and expand the growing interest in this technology and modern polymer chemistry is highly proficient in tailoring polymers with desired properties such as increased mechanical, thermal and chemical stability. Cellulose acetate (CA) is one of the membrane polymers that has been used for aqueous based separation and used as both reverses osmosis (RO) and ultrafiltration (UF) membranes. This paper presents investigation of influence of casting machine speed in membrane preparation. CA is used in this study. That was CA-398-30 with average acetyl content 39.8 wt %. Non solvent used is water and the solvent is 99.7 % organic Dimethyl Sulfoxide (DMSO). The homogenous CA/DMSO solutions were prepared by dissolving CA in DMSO solvent. The CA concentration were varied 13 and 16 % while casting solution speed were varied from 20 to 80 mm/sec with distance cutting machine were fixed at 14 cm. In addition, non solvent in coagulation bath also were varied by 100 % water and 10 % DMSO in water. The results of this experiment describe effect of casting machine speed to water permeability. The effect of CA concentration to water permeability shows the adversative result between 13 and 16 % CA in 100 non solvent water. The similar result also observed in 10 % DMSO in water.